2021
DOI: 10.1172/jci152973
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIa clinical trial of complement C3 inhibitor AMY-101 in adults with periodontal inflammation

Abstract: Background. Gingivitis and periodontitis are prevalent inflammatory diseases of the periodontal tissues. Current treatments are often ineffective or do not prevent disease recurrence.Uncontrolled complement activation and resulting chronic gingival inflammation is a hallmark of periodontal diseases. We determined efficacy and safety of a complement 3-targeted therapeutic, AMY-101, locally administered in adults with periodontal inflammation.Methods. Thirty-two patients with gingival inflammation were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 57 publications
(78 reference statements)
2
52
0
1
Order By: Relevance
“…Notably, periodontitis has been found to be associated with the severity and adverse outcomes of COVID‐19, 13,14 as both diseases are related to extensive perturbation of immune systems (e.g., increased complement activation) 79,96,97 . Most recently, similar therapeutic strategies (e.g., using complement inhibitor AMY‐101) have been evaluated via clinical trials for controlling the two diseases 98,99 . ACE2 and TMPRSS2 are two pivotal players in the infection of SARS‐CoV‐2 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, periodontitis has been found to be associated with the severity and adverse outcomes of COVID‐19, 13,14 as both diseases are related to extensive perturbation of immune systems (e.g., increased complement activation) 79,96,97 . Most recently, similar therapeutic strategies (e.g., using complement inhibitor AMY‐101) have been evaluated via clinical trials for controlling the two diseases 98,99 . ACE2 and TMPRSS2 are two pivotal players in the infection of SARS‐CoV‐2 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, multi-center randomized controlled clinical trials are required to implicate periodontitis as a modifiable risk factor for linked comorbidities. Further improvement of local periodontal treatment via innovative adjunctive hostmodulation approaches, 39,40 such as by modulating complement with the C3-targeted drug AMY-101, which showed efficacy in a recent phase 2a trial in patients with periodontal inflammation, 37,38 may greatly contribute to prevent systemic inflammation and promote overall health.…”
Section: Con Clus I On and Outlookmentioning
confidence: 99%
“…These mechanistic insights, mostly derived from studies in preclinical models, imply that periodontitis is a modifiable risk factor for comorbidities, a notion that is supported by clinical interventional studies, which showed that treatment of periodontitis attenuates systemic inflammation and surrogate markers of comorbidities 34‐36 . Accordingly, emerging adjunctive host‐modulation therapies (eg, complement‐targeted intervention with efficacy in phase 2a trial in patients with periodontal inflammation 37,38 ), to improve periodontal treatment (beyond the level achieved by conventional approaches alone), acquire increased importance, as they could help reduce the risk of systemic comorbidities 39,40 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APL-2 or percetacoplan is in different phases of clinical trials for PNH and age-related macular degeneration (AMD) [ 156 , 157 ]. A novel analog called AMY-101 has yet to reach clinical trials but is in early preparation [ 158 ].…”
Section: Therapies Targeting the Complement Systemmentioning
confidence: 99%